Are mindful people less aggressive? The role of emotion regulation in the relations between mindfulness and aggression. Issue 6 (25th May 2022) - Kim, El‐Lim; Gentile, Douglas A.; Anderson, Craig A.; Barlett, Christopher P.
Abstract: Inducing mindfulness has shown a promising effect on reducing aggression in both clinical and nonclinical populations, possibly because mindfulness can improve emotion regulation. The present study examined the association between mindfulness and aggression through potential mediating effects of several emotion regulation strategies. University and community samples of U.S. adults completed questionnaires on mindfulness, emotion regulation strategies, and trait aggression. Results indicate that mindfulness was associated with rumination and expressive suppression, which mediated the mindfulness‐aggression relationship. Most facets of mindfulness were unrelated to the use of reflection and cognitive reappraisal. The nonjudging of experience facet of mindfulness was negatively related to hostility through rumination and expressive suppression. In contrast, the observing mindfulness facet was positively related to verbal aggression and hostility; these relations were mediated by rumination and expressive suppression.